A novel redox-active metalloporphyrin reduces reactive oxygen species and inflammatory markers but does not improve marginal mass engraftment in a murine donation after circulatory death islet transplantation model. Issue 4 (3rd July 2016) - Bruni, Antonio; Pepper, Andrew R.; Gala-Lopez, Boris; Pawlick, Rena; Abualhassan, Nasser; Crapo, James D.; Piganelli, Jon D.; Shapiro, A. M. James
ABSTRACT: Islet transplantation is a highly effective treatment for stabilizing glycemic control for select patients with type-1 diabetes. Despite improvements to clinical transplantation, single-donor transplant success has been hard to achieve routinely, necessitating increasing demands on viable organ availability. Donation after circulatory death (DCD) may be an alternative option to increase organ availability however, these organs tend to be more compromised. The use of metalloporphyrin anti-inflammatory and antioxidant (MnP) compounds previously demonstrated improved in vivo islet function in preclinical islet transplantation. However, the administration of MnP (BMX-001) in a DCD islet isolation and transplantation model has yet to be established. In this study, murine donors were subjected to a 15-min warm ischemic (WI) period prior to isolation and culture with or without MnP. Subsequent to one-hour culture, islets were assessed for in vitro viability and in vivo function. A 15-minute WI period significantly reduced islet yield, regardless of MnP-treatment relative to yields from standard isolation. MnP-treated islets did not improve islet viability compared to DCD islets alone. MnP-treatment did significantly reduce the presence of extracellular reactive oxygen species (ROS) (p < 0 .05). Marginal, syngeneic islets (200 islets) transplanted under the renal capsule exhibited similar in vivo outcomes regardless of WI or MnP-treatment. DCD islet grafts harvested 7 d post-transplant exhibited sustained TNF-α and IL-10, while MnP-treated islet-bearing grafts demonstrated reduced IL-10 levels. Taken together, 15-minute WI in murine islet isolation significantly impairs islet yield. DCD islets do indeed demonstrate in vivo function, though MnP therapy was unable to improve viability and engraftment outcomes.